The Study of the Effectiveness of Engklek Game in Vocabulary Learning at Primary Schools in Mojokerto - Nuril Badiatus Sa’adah; Nurhayati Ganinda; Wiwik Mardiana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to measure the effectiveness of using the traditional game